Cross-modal interactions of faces, voices and names in person familiarity. Issue 4 (3rd July 2017) - Bao, Jing Ye; Corrow, Sherryse L.; Schaefer, Heidi; Barton, Jason J. S.
ABSTRACT: Person recognition often involves integration of several cues. We asked if familiarity judgments for one cue were influenced by the congruency of pairings with other cues. In a learning phase, subjects studied audiovisual clips of faces, voices and names. A test phase presented uni-modal and bi-modal stimuli. For 10 subjects the bi-modal test stimuli were faces and voices, for 10 faces and names, and for 10 voices and names. In one set of blocks the target was the first modality, and in the other set it was the second. Targets in bi-modal stimuli were paired with either the same or a different identity in the second modality. Face/voice combinations showed congruency effects in reaction time but face/name and voice/name combinations did not. There was no difference between faces modulating target voices and voices modulating target faces. This is consistent with interactions between sensory representations before amodal stages of person recognition.